Immunogenetic mechanisms for the coexistence of organ-specific and systemic autoimmune diseases - Fridkis-Hareli, Masha (BioMed Central, 2008)
BACKGROUND: Organ-specific autoimmune diseases affect particular targets in the body, whereas systemic diseases engage multiple organs. Both types of autoimmune diseases may coexist in the same patient, either sequentially or concurrently, sustained by the presence of autoantibodies directed against the corresponding autoantigens. Multiple factors, including those of immunological, genetic, endocrine and environmental origin, contribute to the above condition. Due to association of certain autoimmune disorders with HLA alleles, it has been intriguing to examine the immunogenetic basis for autoantigen presentation leading to the production of two or more autoantibodies, each distinctive of an organ-specific or systemic disease. This communication offers the explanation for shared autoimmunity as illustrated by organ-specific blistering diseases and the connective tissue disorders of systemic nature. PRESENTATION OF THE HYPOTHESIS: Several hypothetical mechanisms implicating HLA determinants, autoantigenic peptides, T cells, and B cells have been proposed to elucidate the process by which two autoimmune diseases are induced in the same individual. One of these scenarios, based on the assumption that the patient carries two disease-susceptible HLA genes, arises when a single T cell epitope of each autoantigen recognizes its HLA protein, leading to the generation of two types of autoreactive B cells, which produce autoantibodies. Another mechanism functioning whilst an epitope derived from either autoantigen binds each of the HLA determinants, resulting in the induction of both diseases by cross-presentation. Finally, two discrete epitopes originating from the same autoantigen may interact with each of the HLA specificities, eliciting the production of both types of autoantibodies. TESTING THE HYPOTHESIS: Despite the lack of immediate or unequivocal experimental evidence supporting the present hypothesis, several approaches may secure a better understanding of shared autoimmunity. Among these are animal models expressing the transgenes of human disease-associated HLA determinants and T or B cell receptors, as well as in vitro binding studies employing purified HLA proteins, synthetic peptides, and cellular assays with antigen-presenting cells and patient's lymphocytes. Indisputably, a bioinformatics-based search for peptide motifs and the modeling of the conformation of bound autoantigenic peptides associated with their respective HLA alleles will reveal some of these important processes. IMPLICATIONS OF THE HYPOTHESIS: The elucidation of HLA-restricted immune recognition mechanisms prompting the production of two or more disease-specific autoantibodies holds significant clinical ramifications and implications for the development of more effective treatment protocols.